Analisa dan Usulan Perbaikan Layanan Sertifikasi Produk dengan Metode Lean Service - Kacaribu, Loista Sevnin; Tarigan, Uni Pratama; Sembiring, Anita; Budiman, Irwan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Product Certification Service is a service to business actors who want to get their products certified through the Indonesian National Standard Mark User Product Certificate (SPPT SNI), either compulsorily or voluntarily regulated products. Therefore, the Standardization and Industrial Services Center (BSPJI) Medan as a public service unit that has a Product Certification Agency (LSPro) is needed. The problem is the length of the LSPro BSPJI Medan service process to complete the company’s SPPT SNI starting from the application until the issuance of the SPPT SNI. This causes losses for business actors both in funds and time. The purpose of this study is to provide suggestions for improvement and optimize time by maintaining value-added activities and reducing non-value-added activities. The methods used are Lean Service, Waste Analysis and for design using the FVSM Method. The results showed that there was waste that occurred in the LSPro BSPJI Medan service. From the results of the FVSM carried out, there was a reduction in service time from 92 working hours to 26 working hours.